Border Control: Regulating LPS Biogenesis - Guest, Randi L. (Trends Microbiol, 2020)
The outer membrane (OM) is a defining feature of Gram-negative bacteria that serves as a permeability barrier and provides rigidity to the cell. Critical to OM function is establishing and maintaining an asymmetrical bilayer structure with phospholipids in the inner leaflet and the complex glycolipid lipopolysaccharide (LPS) in the outer leaflet. Cells ensure this asymmetry by regulating the biogenesis of lipid A, the conserved and essential anchor of LPS. Here we review the consequences of disrupting the regulatory components that control lipid A biogenesis, focusing on the rate-limiting step performed by LpxC. Dissection of these processes provides critical insights into bacterial physiology and potential new targets for antibiotics able to overcome rapidly spreading resistance mechanisms.